Uridine 5'-Triphosphate Stimulates Alveolar Fluid Clearance in the Isolated Rat Lungs - Tsutomu Sakuma; Xiu Gu; Makoto Sugita; Motoyasu Sagawa; Maki Sakuda; Hirohisa Toga (Elsevier, 2004)
Uridine 5'-triphosphate (UTP) increases chloride secretion followed by fluid movement into the proximal airspaces. However, little is known about whether UTP affects fluid movement in the distal airspaces. We studied the effect of UTP on basal and stimulated alveolar fluid clearance in the isolated rat lungs. Isosmotic 5% albumin solution was instilled into the alveolar spaces of isolated rat lungs, which were then inflated with 100% oxygen at an airway pressure of 7 cmH2O. Alveolar fluid clearance was measured by the progressive increase in albumin concentrations over 1 h. Although UTP (10−9 - 10−6 M) did not increase alveolar fluid clearance, UTP (10−5 - 10−3 M) and isoproterenol (10−5 M), a β-adrenergic agonist, increased alveolar fluid clearance by 40% and 120% of the basal values, respectively. A combined treatment of UTP (10−4 M, 10−3 M) and isoproterenol increased alveolar fluid clearance by 280% of the basal value. The effects of UTP in the presence and absence of isoproterenol were abolished by blockers of a P2 purinoceptor and chloride channels. These results indicate that UTP stimulates alveolar fluid clearance in the distal airspaces of rat lungs.